Le parrainage francophone/francophile comme outil d'intégration académique, sociale et linguistique - Hélène Knoerr
enThis study reports on a program pairing up first-year Anglophone students registered in a French immersion stream with Francophone students enrolled in the same discipline courses delivered in French in a bilingual Canadian university. This program has three main goals : (1) improve immersion students' academic success; (2) facilitate their integration in the student community; (3) improve their French language skills. This collaborative work program was offered during three thirteen week- long terms over two academic years and assessed via Likert-type questionnaires completed by the participants. Although the number of respondents was relatively limited, results indicate that students view the program as a way to improve their language and academic skills and to facilitate their integration into the student community. The program also seems to foster closer ties between the two linguistic and cultural communities.